Synthetic Fluid Inclusions XXIV. In situ Monitoring of the Carbonation of Olivine Under Conditions Relevant to Carbon Capture and Storage Using Synthetic Fluid Inclusion Micro-Reactors: Determination of Reaction Rates - Sendula, Eszter; Lamadrid, Héctor M.; Rimstidt, J. Donald; Steele-MacInnis, Matthew; Sublett, D. Matthew; Aradi, László E.; Szabó, Csaba; Caddick, Mark J.; Zajacz, Zoltán; Bodnar, Robert J. (Frontiers in Climate, 2021)
Ultramafic and mafic rocks are possible targets for CO2 sequestration via mineral carbonation. The determination of reaction kinetics and the factors that control mineralization are important in order to understand and predict how fast injected CO2 will react with host rocks to permanently isolate and store the carbon. Here we present experimental results of olivine carbonation experiments using synthetic fluid inclusions (SFI) as micro-reactors. The micro-reactor technique coupled with non-destructive Raman spectroscopy allows us to monitor the reaction progress in situ and in real time at elevated temperatures (50–200°C) and pressures (several 10's to a few hundred bars), and quantify the amount of CO2 consumed in the reaction using the Raman CO2 densimeter and mass-balance calculations. Results show a measurable decrease of CO2 density in the fluid inclusions as a result of the reaction between the CO2-bearing seawater-like aqueous solution and olivine. Magnesite formation was observed within hours at ≥100°C, while at 50°C magnesite nucleation and precipitation was only observed after a few weeks. Raman mapping and FIB-SEM analysis confirmed the formation of a non-continuous Si-rich layer on the inclusion wall and the presence of ferroan magnesite as a reaction product. Reaction rates [log J (mol/m−2 s−1)] obtained for olivine carbonation range between ~-8.4 at 50°C and −4.7 at 200°C, which is sufficiently rapid to be suitable for commercial CO2 injection projects. Reaction rates involving a seawater-like fluid were similar to rates published for high salinity solutions containing NaHCO3, and were faster compared to rates involving solutions with low salinity. Thus, CO2 injection into submarine environments might offer some advantages over CO2 storage in onshore basalts where the pores are likely to be filled with low salinity meteoric water. The application of the synthetic fluid inclusion technique, combined with non-destructive analytical techniques, is a promising tool to monitor rates of fluid-rock reactions in situ and in real time. Here, we have documented its application to experimentally study carbonation reactions in the olivine-H2O-CO2-NaCl-MgCl2 system.